Wrocław Tourist Lines: The changing nature of its offer and the tourist product life cycle - Kołodziejczyk, Krzysztof (Turyzm/Tourism, 2022)
Tourist lines serviced by historic vehicles function in several cities. One of them is Wrocław (Poland) in which the current offer based on trams was extended with buses in 2021. In the article, an assessment of Wrocław Tourist Lines has been carried out regarding the tourist product and its development, while additionally determining its stage in the product life cycle. To this end, among other elements, data on the number of passengers and ticket sales have been used. After 13 years of existence, the offer has developed traits of a mature product, displaying fairly stable journey figures. However, it did not use the significant potential of the heritage public transport fleet in Wrocław to the full. That is why, in recent years, several changes have been introduced to the structure, marketing and pricing of the tourist product, which have improved journey frequencies and, even more importantly, increased the passenger rate per service. Therefore, it can be claimed that as a result of the actions undertaken, the product has entered a rejuvenation stage, but this process is still fairly unmarked. The main disadvantage of the product is its marketing and the way the offer is communicated to potential passengers.